The Effect of Back Massage For Health: Literature Review - Arsita, Rachmah Dara; Sari, RIna Puspita; Wibisono, Winisono (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Health is a state of overall being, no just disease and weakness. Health efforts must be directed so that every human being has adequate health, pharmacological and non-pharmacological treatments can be one of the efforts to maintain health. Non pharmacological therapy that can be used is back massage. Back massage in the complementary therapy of manipulation practice because touch and pressure provide health effect. This study aimed to determine the use of back massage for health. This study use Literature review with a prisma approach amounting to 9 journals. The results of this study that have been analyzed show back massage is very effective for health, especially can improve sleep quality, reduce pain intensity, accelerate milk production, and improve cognitive. Giving back massage is very effective for non-pharmacological therapy